PENGARUH SENAM OTAK TERHADAP PERUBAHAN DAYA INGAT (FUNGSI KOGNITIF) PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA ILOMATA KOTA GORONTALO TAHUN 2017 - Rosmin Ilham; Firmawati Firmawati (-, 2021)
This research was conducted at Tresna Werdha social house Ilomata Gorontalo city. The objective is to find out the influence of brain training on memory changes (cognitive function) in elderly. The design of the research is quasi experiment with one group pre test post test design, with purposive sampling technique. The sample of the research is the elderly at Tresna Werdha social house Ilomata Gorontalo city with 20 respondents.  The data collection tools used mini mental status examination. Statistical test analysis used paired sample test. Statistical test result obtained P value 0,000 means that P value less than alpha (P<0,05) which means Ho is rejected, therefore it can be concluded taht, there is the influence of brain training on memory changes (cognitive function) in elderly at Tresna Werdha social house Ilomata Gorontalo city.